Teorema Hahn-Banach untuk Fungsional Linier Terbatas - Astuti, Rahmadita Widya; Maharani, Dian; Aziz, Abdul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
A linear functional is a mapping from a vector space to a field , ( or ), that satisfies two properties, additivity and homogeneity. Among the various properties of linear functionals, one important property is boundedness. This research is to prove the boundedness property of linear functionals using the Hahn-Banach Theorem. The Hahn-Banach Theorem addresses the extension of linear functionals. Thus, the results of this research show that with the Hahn-Banach Theorem, every element in a normed space can be associated with a bounded linear functional such that dan . Furthermore, a linear functional defined on a real vector space can be extended to a complex vector space using the structure , and it is proven that this extension satisfies . This research is expected to be beneficial and serve as an additional reference.